PHYSICOCHEMICAL PROPERTIES OF REFINED SOYBEAN OIL AND DEODORIZER DISTILLATE AS BIODIESEL FEEDSTOCKS - Olafimihan, Blessing Ayomide; Esan, Akintomiwa Olumide; Ishola, Kayode Taiwo; Shittu, Monsurat Olabisi Atunnise; Adetayo-Balogun, Aminat Adebisi (FUDMA JOURNAL OF SCIENCES, 2025)
Biodiesel is an eco-friendly fuel that possesses the right qualities as a renewable source of energy including excellent lubricity, high flash point and biodegradability and this mainly depends on the raw material used. Hence, the physicochemical properties of refined soybean oil and soybean oil deodorizer distillate were determined to compare the most suitable for biodiesel production. The physicochemical parameters of the two oils which include: acid, iodine, saponification, free fatty acid and peroxide value, were determined by the official standard method of the Association of Official Analytical Chemists. The results revealed free fatty acid, peroxide, acid, iodine, and saponification content of soybean oil deodorizer distillate to be: 47.70±1.00 mg KOH/g, 248.55±0.89 meq O2/kg, 115.69±0.85 mg KOH/g, 5.58±0.51 g I2/100 g, and 64.95±0.65 mg KOH/g. While that of refined soybean oil showed the content to be 0.63±0.11 mg KOH/g, 4.08±1.02 meq O2/kg, 10.33±1.53 mg KOH/g, 11.58±0.38 g I2/100 g, and 34.70±1.00 mg KOH/g. These results indicate the free fatty acid, peroxide, acid and saponification content of soybean oil deodorizer distillate to be higher compared to refined soybean oil which suggests that it may require further pretreatment prior to transesterification. Although no transesterification reactions were conducted in this research, the high FFA Content and the origin of soybean oil deodorizer distillate as a byproduct of oil refining suggest its potential as a cost-effective and sustainable feedstock for biodiesel production, particularly within a waste valorization framework.